Indirect determination of dopamine and paracetamol by electrochemical impedance spectroscopy using azo coupling reaction with oxidized 2,4-dinitrophenylhydrazine (DNPH): Application in commercial tablets - Boumya, W. (H. : ĐHQGHN, 2020)
A new method for the determination of dopamine (DA) and paracetamol (PCT), based on the azo “coupling reaction with oxidized 2,4 dinitrophenylhydrazine (DNPH), has been established. This method was based on the fact that in the HCl buffer solution, potassium ioadate oxidized 2,4- dinitrophenylhydrazine to form the diazonium chloride at 0e5 C and then the diazonium ion reacted with the phenolic compounds to form azo-compounds. The products of the azo coupling reaction were characterized by UV/Vis spectrophotometry, infrared spectroscopy and square wave voltammetry. Using a MeOH/Water buffer solution (pH 9.0) and electrochemical impedance spectroscopy, DA and PCT were determined in the concentration range of 0.1e1000 mmol L 1, with limits of detection of 0.47 and 0.25 mmol L 1, respectively. The proposed method was successfully applied to the individual determination of DA and PCT in various pharmaceutical formulas, showing the practical feasibility of the proposed method as a novel platform for the sensitive determination of these phenolic compounds.